Conservation biology of the threatened Killarney Fern (Trichomanes speciosum Willd.) in Ireland - Ní Dhúill, Emer (Trinity College (Dublin, Ireland). Department of Botany, 2014)
Killarney Fern (Trichomanes speciosum Willd.) is a rare fern species which is listed on Annex II and IV of the EU Habitats Directive (Council Directive 92/43/EEC) and the Irish Flora Protection Order (1999). T. speciosum is most abundant in the Azores, outside of which is it most frequently found in Ireland and Britain. A species action plan for T. speciosum in Ireland (2008) highlighted the need to monitor existing populations, to determine the conservation status of the Irish populations and to assess the genetic variability of this species in Ireland. The research aimed to fulfil the aspirations of the species action plan (2008) and also to develop a monitoring protocol to help fulfil national obligations on reporting under the EU Habitats Directive.
Embargo End Date: 2019-12-01
Keywords: Natural Sciences, Ph.D.; Ph.D. Trinity College Dublin, 2014